El plomo de Gádor, nueva lectura y análisis (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
This article will first address the historiographical dimension of the Gádor Lead, showing how perceptions of the piece have evolved up to the present day. Despite advances in its study, numerous doubts, discrepancies among researchers, and unresolved elements still persist. The debated aspects include the correct transcription of the signs, the possible existence of scribal errors, the identification of the missing sign at the beginning of the text, the structure of the message, words of uncertain Iberian attribution, possible anthroponyms, the exact location of the discovery, and the content of the text.
Keywords: Gádor; Iberian lead; Iberian language; Palaeohispanic writing systems; Iberian epigraphy